Profile and overload of informal caregivers of dependent elderly people - Conceição, Haylane Nunes da (2021)
Objective: To assess the profile and burden of informal caregivers of dependent elderly people. Methodology: This is a cross-sectional and descriptive study, carried out with informal caregivers of dependent elderly people registered in the area covered by four Basic Health Units in the city of Caxias, Maranhão. Data were collected from June to October 2019, through a questionnaire prepared by the researchers to characterize the participants and by applying the Brazilian version of the Zarit Burder Interview scale. Results: The study population consisted of 52 caregivers. The role of caregiver was most often exercised by female caregivers (n = 47; 90.4%), aged 41 to 50 years old (n = 21; 40.4%), married (n = 32 ; 61.3%), with incomplete elementary education (n = 23; 44.2%), with children (n = 22; 42.3%) being the main caregivers. Most caregivers performed the function for more than four years (n = 19; 36.5%), dedicating more than eight hours of daily assistance to the elderly (n = 22; 42.3%) and did not receive support from other people in care (n = 49; 94.2%). It was also found that most caregivers had some level of burden (n = 47; 90.4%). Conclusion: Information regarding the profile and level of burden of informal caregivers may raise the awareness of Primary Care professionals in the municipality about the impacts of care for dependent elderly people on the health of their caregivers, contributing to the planning of strategies that ensure quality of life. and the health of this population.